Effect of Deficit Irrigation, Planting Date and Biofertilizers on Agro- Morphological Traits, Leaf Nitrogen and Carbon Concentration and Seed Yield on Quinoa under Ardabil conditions - M Jabbari oranj; H Moghaddam; M. R Jahansuz; A Ahmadi; B Motesharezadeh (پژوهشهای زراعی ایران, 2023)
IntroductionThe most important problem that threatens food security of any country and the world is the lack of adequate water resources, so one of the ways to deal with this crisis is to use plants with low water requirements and high water use efficiency. Among the plants, we can name Quinoa, which is one of the plants that has been less studied and exploited in Iran. Since the planting date has the greatest impact on the physiological characteristics of the crop compared to other cropping treatments, so choosing the appropriate planting date can also create the greatest correlation between plant growth trends and climatic conditions. Undoubtedly, the use of biological fertilizers, in addition to the positive effects it has on all soil properties, is also economically, environmentally and socially fruitful and can be a suitable and desirable alternative to chemical fertilizers. Therefore, the aim of this study was to determine the response to deficit irrigation, planting date and application of different biofertilizers in quinoa.Materials and MethodsThis experiment was carried out during two cropping years 2019 and 2020 in a farm located in Moghan region. The site has latitude of 39◦27 N, a longitude of 48◦12 E and is 120 m above mean sea level, with an average annual rainfall of 250-300 mm. In this experiment, Titicaca cultivar of quinoa was cultivated in summer in the form of a double split plot design based on a randomized complete block design with three replications. Experimental factors include irrigation at three levels (Conventional irrigation, Irrigation cut-off in budding stage and Irrigation cut-off in seed filling stage) as a main factor, planting date at three levels (27 July, 11  and 27 August) as a sub-factor and four levels of nitrogen biofertilizer (without inoculation, seed inoculation with Azotobacter, seed inoculation with Azospirillum and inoculation with a mixture of Azotobacter and Azospirillum) were considered as a sub-sub-factor. Plant height, stem diameter and panicle length in each plant were measured at the physiological maturity stage by randomly selecting 10 plants using a ruler with millimeter accuracy. Leaf area was measured by selecting 5 plants from each plot randomly and with the model Leaf area meter Li-cor. At the end of the growing season, the product of two middle planting lines with a length of 4 meters was harvested by observing the half-meter margin effect and after drying in a ventilated oven at 70 °C for 24 hours, grain yield was determined. Leaf carbon concentration was estimated by dry combustion with air flow in an electric furnace, Kjeldahl method (Sharpe et al., 2001) was used to measure nitrogen concentration. Experimental data were analyzed before analysis of variance for homogeneity of test errors through Bartlett test and then analyzed using SAS (9.1) software and comparison of means at 5% probability level using Duncan multi-range test.Results and DiscussionThe results showed that conventional irrigation with planting date of 27 August and inoculation of Azotobacter and Azospirillum biofertilizers had the best effect in terms of morphological traits and leaf nitrogen concentration and The highest grain yield (304.97 g.m-2) was obtained from conventional irrigation treatment with planting date of 27 August and inoculation of biofertilizers of Azotobacter and Azospirillum. Also, quinoa seed yield had a positive and significant correlation with plant height (r = 0.85), stem diameter (r =0. 64), leaf area (r = 0.86), panicle length (r = 0.86) and leaf carbon concentration (r = 0.38) showed.ConclusionThe results of this study showed though conventional irrigation with planting date of 20 August and inoculation of Azotobacter and Azospirillum biofertilizers had the highest number of studied traits, especially grain yield (304.97 g.m-2), but with interruption of irrigation treatment at the stage of seed filling with planting date of 20 August and inoculation of biofertilizers were included in a statistical group, so in terms of the importance of water consumption, it can be said that in conditions of limited water resources, irrigation cut-off treatment in the stage of grain filling has the most favorable results.